The Effects of Promotions, Trust, and Transaction Convenience on Shopee User Satisfaction: A Study Among Students at Stiesia Surabaya) - Musyaffa, Farrel Enrico; Kusuma, Emeralda Ayu (Green Publisher Indonesia, 2026)
This research determines and examines the effect of promotion, trust, and ease of transaction on Shopeecustomers’ satisfaction for students of STIESIA Surabaya. Furthermore, the population consists of students of STIESIA Surabaya who are Shopee customers. The research applies quantitatively. The independent variables included Promotion, trust, and ease of transaction. Meanwhile, customers’ satisfaction was a dependent variable. The data were collected using purposive sampling with a questionnaire and Likert scale. Moreover, multiple linear regression with SPSS (Statistical Product and Service Solution) was used as the data analysis technique. As a result, it indicates that promotion has a positive and significant effect, trust, and ease of transaction have a positive and significant effect on Shopee customers’ satisfaction, with promotion as the most dominant variable.